Synthesis of Cu2O, Cu2O/Charcoal, and Cu2O/Activated Charcoal Composites as Antibacterial Agents - Zaenal Abidin; Wahyu Riski Rahmawati; Irma Isnafia Arief; Eti Rohaeti (Institut Pertanian Bogor, 2024)
The excessive use of antibiotics to treat bacterial infections can lead to bacterial resistance, necessitating other antibacterial agents as alternatives. This research combined charcoal and activated charcoal with metal oxide, namely copper oxide (Cu2O), which has antibacterial properties against Gram-positive and Gram-negative bacteria, thus producing an antibacterial composite for water treatment processes. Furthermore, this study also examined the effect of different types of sugar as reducing agents on the produced Cu2O and identified the antibacterial activity of Cu2O and its composites. Synthesis of Cu2O through the Tollens-like reaction method using Cu(NO3)2 as a precursor, then adding NaOH, NH4OH, and sugar. The sugars were sucrose, white sugar, and brown sugar. The type of sugar used as a reducing agent affected the size and morphology of the Cu2O produced. Adding Cu2O to charcoal and activated charcoal increased antibacterial properties to charcoal and activated charcoal. Copper oxide, Cu2O/charcoal, and Cu2O/activated charcoal exhibited high antibacterial properties against Escherichia coli (Gram-negative), as of 5.69 ± 0.02 mm and 6.23 ± 0.03 mm, respectively, due to their thinner cell walls compared to Staphylococcus aureus (Gram-positive). The Cu2O synthesized using white sugar as the reducing agent showed the best antibacterial activity, with an 8.26 ± 0.19 mm inhibition zone. Keywords: activated charcoal, antibacterial, charcoal, copper oxide, sugar